Is there short-term adaptation to repeated thermal stress relief and pleasure? First insights from an experimental study - Marcel Schweiker; Karin Schakib-Ekbatan; Bhavya Swapneel Pathak; Hannah Pallubinsky; Susanne Becker (Building and Environment, 2026)

INSTINCT: a flow-based open-source PNT framework for satellite navigation and sensor fusion - Thomas Topp; Marcel Maier; Thomas Hobiger; Doris Becker (GPS Solutions, 2025)
INS toolkit for integrated navigation concepts and training (INSTINCT) is an open-source positioning, navigation and timing (PNT) framework for global navigation satellite system (GNSS) navigation and sensor fusion written in C++. It uses flow-based programming to encapsulate functionality, enforce clean interfaces and promote reusability. Not only multi-constellation, multi-frequency single point positioning (SPP) and real-time kinematic positioning (RTK) algorithms are available, but also inertial navigation system (INS)/GNSS sensor fusion. Moreover, innovative concepts like multi inertial measurement unit (IMU) arrays and factor graph optimization are featured. Furthermore, most file formats common in the PNT field can be read with the software and converted between them. Also, simulation of trajectories and IMU data with different error models is possible. A graphical user interface allows the user to directly set parameters and analyze results in plots, which enables rapid prototyping and testing. A developer can easily extend the functionality with own algorithms and sensor interfaces building upon the existing modules. In order to evaluate the performance of the algorithms two experiments were performed. Analysis of a static dataset shows that the position accuracy of the RTK algorithm of INSTINCT is comparable to RTKLIB. Additionally, a dynamic dataset was generated using a Spirent GNSS simulator and INSTINCT’s IMU simulation capabilities. In-depth assessment confirms the high accuracy of the results and demonstrates that the INS/GNSS loosely coupled Kalman filter can compensate for GNSS outages.

Recycling processes of polyester-containing textile waste–A review - Jana Enking; Amrei Becker; Gilbert Schu; Marcel Gausmann; Stefano Cucurachi; Arnold Tukker; Thomas Gries (Resources, Conservation and Recycling, 2025)

Nature 4.0: A networked sensor system for integrated biodiversity monitoring - Dirk Zeuss; Lisa Bald; Jannis Gottwald; Marcel Becker; Hicham Bellafkir; Jörg Bendix; Phillip Bengel; Larissa T. Beumer; Roland Brandl; Martin Brändle; Stephan Dahlke; Nina Farwig; et al. (Global Change Biology, 2024)
Ecosystem functions and services are severely threatened by unprecedented global loss in biodiversity. To counteract these trends, it is essential to develop systems to monitor changes in biodiversity for planning, evaluating, and implementing conservation and mitigation actions. However, the implementation of monitoring systems suffers from a trade‐off between grain (i.e., the level of detail), extent (i.e., the number of study sites), and temporal repetition. Here, we present an applied and realized networked sensor system for integrated biodiversity monitoring in the Nature 4.0 project as a solution to these challenges, which considers plants and animals not only as targets of investigation, but also as parts of the modular sensor network by carrying sensors. Our networked sensor system consists of three main closely interlinked components with a modular structure: sensors, data transmission, and data storage, which are integrated into pipelines for automated biodiversity monitoring. We present our own real‐world examples of applications, share our experiences in operating them, and provide our collected open data. Our flexible, low‐cost, and open‐source solutions can be applied for monitoring individual and multiple terrestrial plants and animals as well as their interactions. Ultimately, our system can also be applied to area‐wide ecosystem mapping tasks, thereby providing an exemplary cost‐efficient and powerful solution for biodiversity monitoring. Building upon our experiences in the Nature 4.0 project, we identified ten key challenges that need to be addressed to better understand and counteract the ongoing loss of biodiversity using networked sensor systems. To tackle these challenges, interdisciplinary collaboration, additional research, and practical solutions are necessary to enhance the capability and applicability of networked sensor systems for researchers and practitioners, ultimately further helping to ensure the sustainable management of ecosystems and the provision of ecosystem services.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Unintentional guideline deviations in hospitalized patients with two or more antithrombotic agents: an intervention study - Renate C. A. E. van Uden; Marcel P. H. van den Broek; Ilse Houtenbos; Tessa C. C. Jaspers; Ankie M. Harmsze; Hylke J. Kingma; Diego A. M. Odekerken; Karina Meijer; Patricia M. L. A. van den Bemt; Matthijs L. Becker (European Journal of Clinical Pharmacology, 2021)
Purpose Treatment schedules for antithrombotic therapy are complex, and there is a risk of inappropriate prescribing or continuation of antithrombotic therapy beyond the intended period of time. The primary aim of this study was to determine the frequency of unintentional guideline deviations in hospitalized patients. Secondary aims were to determine whether the frequency of unintentional guideline deviations decreased after intervention by a pharmacist, to determine the acceptance rate of the interventions and to determine the type of interventions. Methods We performed a non-controlled prospective intervention study in three teaching hospitals in the Netherlands. We examined whether hospitalized patients who used the combination of an anticoagulant plus at least one other antithrombotic agent had an unintentional guideline deviation. In these cases, the hospital pharmacist contacted the physician to assess whether this deviation was intentional. If the deviation was unintentional, a recommendation was provided how to adjust the antithrombotic regimen according to guideline recommendations. Results Of the 988 included patients, 407 patients had an unintentional guideline deviation (41.2%). After intervention, this was reduced to 22 patients (2.2%) (p < 0.001). The acceptance rate of the interventions was 96.6%. The most frequently performed interventions were discontinuation of an low molecular weight heparin in combination with a direct oral anticoagulant and discontinuation of an antiplatelet agent when there was no indication for the combination of an antiplatelet agent and an anticoagulant. Conclusion A significant number of hospitalized patients who used an anticoagulant plus one other antithrombotic agent had an unintentional guideline deviation. Intervention by a pharmacist decreased unintentional guideline deviations.

Host dispersal shapes the population structure of a tick‐borne bacterial pathogen - Ana Cláudia Norte; Gabriele Margos; Noémie S. Becker; Jaime Albino Ramos; Maria Sofia Núncio; Volker Fingerle; Pedro Miguel Araújo; Peter Adamík; Haralambos Alivizatos; Emilio Barba; Rafael Barrientos; Laure Cauchard; et al. (Molecular Ecology, 2020)
Birds are hosts for several zoonotic pathogens. Because of their high mobility, especially of longdistance migrants, birds can disperse these pathogens, affecting their distribution and phylogeography. We focused on Borrelia burgdorferi sensu lato, which includes the causative agents of Lyme borreliosis, as an example for tick‐borne pathogens, to address the role of birds as propagation hosts of zoonotic agents at a large geographical scale. We collected ticks from passerine birds in 11 European countries. B . burgdorferi s.l. prevalence in Ixodes spp. was 37% and increased with latitude. The fieldfare Turdus pilaris and the blackbird T. merula carried ticks with the highest Borrelia prevalence (92 and 58%, respectively), whereas robin Erithacus rubecula ticks were the least infected (3.8%). Borrelia garinii was the most prevalent genospecies (61%), followed by B. valaisiana (24%), B. afzelii (9%), B. turdi (5%) and B. lusitaniae (0.5%). A novel Borrelia genospecies “ Candidatus Borrelia aligera” was also detected. Multilocus sequence typing ( MLST ) analysis of B. garinii isolates together with the global collection of B. garinii genotypes obtained from the Borrelia MLST public database revealed that: (a) there was little overlap among genotypes from different continents, (b) there was no geographical structuring within Europe, and (c) there was no evident association pattern detectable among B. garinii genotypes from ticks feeding on birds, questing ticks or human isolates. These findings strengthen the hypothesis that the population structure and evolutionary biology of tick‐borne pathogens are shaped by their host associations and the movement patterns of these hosts.

Altered orbitofrontal activity and dorsal striatal connectivity during emotion processing in dependent marijuana users after 28 days of abstinence - Kaeli Zimmermann; Shuxia Yao; Marcel Heinz; Feng Zhou; Wolfgang Dau; Markus Banger; Bernd Weber; René Hurlemann; Benjamin Becker (Psychopharmacology, 2018)

Natural variation in life history strategy of Arabidopsis thaliana determines stress responses to drought and insects of different feeding guilds - Nelson H. Davila Olivas; Enric Frago; Manus P. M. Thoen; Karen J. Kloth; Frank F. M. Becker; Joop J. A. van Loon; Gerrit Gort; Joost J. B. Keurentjes; Joost van Heerwaarden; Marcel Dicke (Molecular Ecology, 2017)
Plants are sessile organisms and, consequently, are exposed to a plethora of stresses in their local habitat. As a result, different populations of a species are subject to different selection pressures leading to adaptation to local conditions and intraspecific divergence. The annual brassicaceous plant Arabidopsis thaliana is an attractive model for ecologists and evolutionary biologists due to the availability of a large collection of resequenced natural accessions. Accessions of A. thaliana display one of two different life cycle strategies: summer and winter annuals. We exposed a collection of 308 European Arabidopsis accessions, that have been genotyped for 250K SNPs, to a range of stresses: one abiotic stress (drought), four biotic stresses ( Pieris rapae caterpillars, Plutella xylostella caterpillars, Frankliniella occidentalis thrips and Myzus persicae aphids) and two combined stresses (drought plus P. rapae and Botrytis cinerea fungus plus P. rapae ). We identified heritable genetic variation for responses to the different stresses, estimated by narrow‐sense heritability. We found that accessions displaying different life cycle strategies differ in their response to stresses. Winter annuals are more resistant to drought, aphids and thrips and summer annuals are more resistant to P. rapae and P. xylostella caterpillars. Summer annuals are also more resistant to the combined stresses of drought plus P. rapae and infection by the fungus Botryris cinerea plus herbivory by P. rapae . Adaptation to drought displayed a longitudinal gradient. Finally, trade‐offs were recorded between the response to drought and responses to herbivory by caterpillars of the specialist herbivore P. rapae .

Reciprocal regulation of 11β-hydroxysteroid dehydrogenase 1 and glucocorticoid receptor expression by dexamethasone inhibits human coronary artery smooth muscle cell proliferation in vitro - George Michas; Marcel Liberman; Kristian C. Becker; Diane E. Handy; Joseph Loscalzo; Jane A. Leopold (Molecular and Cellular Biochemistry, 2011)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)